PENGGUNAKAN MEDIA KOMPUTER DENGAN PERANGKAT LUNAK AUTODESK INVENTOR UNTUK MENINGKATKAN HASIL BELAJAR MATA DIKLAT MENGGAMBAR TEKNIK MANUFAKTUR KELAS XI PROGRAM KEAHLIAN TEKNIK PEMESINAN DI SMK NEGERI 2 PALEMBANG - Syafrudin, Syafrudin (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to develop computer-based learning devices with Autodesk Inventor software that is implemented in class XI machining engineering expertise programs, in the hope of increasing student mastery learning. The learning completeness indicator is that if a student obtains a score of at least 7.0 or 70% for productive education eyes and classically has obtained a value of at least 85% of the number of students in that class who have achieved an individual score of 70%. The results of the study show the following: for the assessment of the conventional method of 35 students, a range of values of less than 70 has been obtained by 24 students (68.57%) and a range of values of more than 70 as many as 11 students (31.53%). The assessment carried out by the method of using computer media with Autodesk Inventor software from 35 students has obtained a range of values of less than 70 as many as 5 students (14.29%) and a value range of more than 70 as many as 30 students (85.71%). From these data, it can be concluded that the eye learning training draws machine skills using the method of using computer media with Autodesk Inventor software significantly better when compared with learning using conventional methods.